2019
DOI: 10.7150/thno.33141
|View full text |Cite
|
Sign up to set email alerts
|

An in situ microenvironmental nano-regulator to inhibit the proliferation and metastasis of 4T1 tumor

Abstract: Tumor microenvironment, such as hypoxia and presence of immune cells, plays a critical role in cancer initiation, growth as well as progression, and seriously affects antitumor effect. Accordingly, we constructed a kind of multifunctional nanoparticles (NPs) with macrophage transformation and oxygen (O 2 ) generation characteristics, to regulate the tumor microenvironment. Methods: In this study, we synthesized mesoporous Prussian blue (MPB) NPs with low molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 31 publications
(39 reference statements)
0
39
0
1
Order By: Relevance
“…Ultrasound irradiation induces the production of H 2 O 2 from HMME and MPB acts as a catalyst of hydrogen peroxide (H 2 O 2 ) to produce O 2 . In vivo experiments using 4T1 tumor-bearing mice showed that ultrasound irradiation of LMWHA-MPB/HMME induced both the production of O 2 and the transformation of the tumor microenvironment 229 .…”
Section: Macrophage As Theranostic Toolsmentioning
confidence: 98%
See 1 more Smart Citation
“…Ultrasound irradiation induces the production of H 2 O 2 from HMME and MPB acts as a catalyst of hydrogen peroxide (H 2 O 2 ) to produce O 2 . In vivo experiments using 4T1 tumor-bearing mice showed that ultrasound irradiation of LMWHA-MPB/HMME induced both the production of O 2 and the transformation of the tumor microenvironment 229 .…”
Section: Macrophage As Theranostic Toolsmentioning
confidence: 98%
“…Low-molecular-weight hyaluronic acid (LMWHA) also promotes M1 macrophage polarization 228 . Based on LMWHA, multifunctional nanoparticles were developed to combine macrophage reprogramming and modulation of the microenvironment for cancer therapy 229 . Mesoporous Prussian blue nanoparticles (MPB) were coated with LMWHA and used as a cargo for sonosensitizer hematoporphyrin monomethyl ether (HMME).…”
Section: Macrophage As Theranostic Toolsmentioning
confidence: 99%
“…With regard to energy metabolism, cancer cells with high glycolytic activity decrease the availability of glucose and induce an acidic microenvironment, which push TAMs towards an M2-like metabolism, strongly committed to oxidative phosphorylation and fatty acid oxidation, in contrast to M1-like macrophages, which present higher glucose uptake and aerobic glycolytic catabolism [ 182 ]. To alleviate hypoxia, hyaluronic acid NPs targeted towards TAMs have been designed to increase O 2 production in the TME, showing inhibition of tumor growth and metastasis in 4T1 tumors [ 183 , 184 ]. Inactivation of HIF-1α by restoring miR-30c expression in macrophages showed antitumoral efficacy in gastric cancer [ 185 ].…”
Section: Metabolic Manipulation To Reprogram Tamsmentioning
confidence: 99%
“…This approach demonstrated that LMWHA-MPB penetrates M2 macrophages (pro-tumoral macrophages), which are subsequently diverted toward the M1 phenotype exhibiting anti-tumoral action. Therefore, LMWHA-MPB can induce TAMs pro-tumoral potential and can likewise be used in situ for microenvironmental tumoral regulation [ 250 ].…”
Section: Gags and Immunological Aspects Of Cancer Therapymentioning
confidence: 99%